Analyzing the financial performance and its potential for TNB by using fundamental and technical analysis / Sharifah Arni Syed Jaaffar, Noor Emmiey Shafieza Sazali and Nur Afzan Mohd Zulkifli - Syed Jaaffar, Sharifah Arni; Sazali, Noor Emmiey Shafieza; Mohd Zulkifli, Nur Afzan (2014)
The purpose of this research paper is using financial tools to analyse and provide an overview of financial performance of Tenaga Nasional Berhad. After analyzing the information i.e 10 years (2003-2012) of Annual Reports such as balance sheet and also income statement, this research paper is to investigate the issue of rising tariff imposed to the user even though TNB’s financial performance was getting better each year. This research paper also seeks to determine which factors give the highest affect to its financial performance. Besides that this research paper will provide TNB a guidance to make decisions required on managing their business and to develop their future financial plans which requires reliable and pertinent information on the financial performance and financial position of the firm although if the analysis forecasts serious financial problems. Our paper analyzes the financial performance for TNB using Fundamental and Technical analysis. The method of calculating Fundamental analysis is using formula of ratio while technical analysis, the application of MetaStock is needed to analyze broad market conditions to help investors whether they should invest in TNB or not. While it could provides information to the public on the financial performance of TNB for each year. MetaStock application is been used to analyze an individual securities (stocks, futures, mutual funds, etc.). In response to the increasing demand for a real-time analysis of prices.